Perkembangan Penelitian di Bidang Teknologi Membran Menggunakan Pendekatan Cellulose Acetate Mixed Matrix Membrane: Studi Analisis Bibliometrik - Panggulu Ahmad Ramdhani Utoro; Imam Rosadi (Universitas Batanghari Jambi, 2022)
The development of science needs to be done so that research gaps can be traced and known so that sustainable research occurs. In this study, a bibliometric analysis approach was carried out with the keywords